Construction of functional surfaces for dental implants to enhance osseointegration - Wang, Zhenshi; Wang, Jiaolong; Wu, Runfa; Wei, Junchao (Frontiers in Bioengineering and Biotechnology, 2023)
Dental implants have been extensively used in patients with defects or loss of dentition. However, the loss or failure of dental implants is still a critical problem in clinic. Therefore, many methods have been designed to enhance the osseointegration between the implants and native bone. Herein, the challenge and healing process of dental implant operation will be briefly introduced. Then, various surface modification methods and emerging biomaterials used to tune the properties of dental implants will be summarized comprehensively.